Evil Intuitions? The Problem of Evil, Experimental Philosophy, and the Need for Psychological Research - Michael Church, Ian (Journal of psychology and theology, 2021)
The primary aim of this article is to highlight, at least in short, how the resources of experimental philosophy could be fruitfully applied to the evidential problem of evil. To do this, we will consider two of the most influential and archetypal formulations of the problem: William L. Rowe’s article, “The problem of evil and some varieties of atheism” (1979), and Paul Draper’s article, “Pain and pleasure: an evidential problem for theists” (1989). We will consider the relevance of experimental philosophy to Rowe’s 1979 argument in §1 and to Draper’s 1989 argument in §2. But in addition to exploring how the resources of experimental philosophy might apply to the problem of evil, it is also worth exploring what broader empirical factors might contribute to people having the intuitions that they have—from someone’s affective state to someone’s need for closure. In §3, we want to very briefly elucidate a few areas where the psychology of philosophy might be productively explored in future empirical research.